Insights into ethnoveterinary practices used by various communities in Dhemaji district of Assam - Prajwalita Pathak; Gunjan Gogoi
A study was carried out for documentation of ethnoveterinary practices prevalent among the various communities of the Dhemaji district of Assam. Personnel interviews, questionnaires, participatory rural appraisal, group discussions, and field visits were followed to collect the data. A total of 250 livestock farmers were selected across the district from 25 villages. The degree of adoption and effectiveness of each ethnoveterinary practice were expressed in percentage considering the responses of sampled farmers. A total of 62 ethnoveterinary practices were recorded where 43 plant species of 30 families were used to treat 33 common ailments in livestock and poultry. The highest, 28 practices were used for treatments of cattle followed by 21 for treatments of pigs, 8 for poultry, and 5 for Goat against the common issues related to the digestive system, fever, parasitic infestation, viral infection, bone fracture, retention of placenta (ROP), weakness and other health condition in livestock and poultry where the adoption was ranged from 6.00 to 89.33 percent. The present documentation will help the researchers, environmentalists, and other stakeholders towards better understanding in traditional knowledge, distribution of valuable resources and biodiversity conservation of the district.